2014
DOI: 10.1021/cg500752x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correspondence of Solution, Liquid Crystal, and Crystalline Phases of the Chromonic Mesogen Sunset Yellow

Abstract: The azo dye, sunset yellow, is a prototypical, chromonic liquid crystal in which assembly in aqueous solution at high volume fraction leads to lyotropic mesophases with a "package of properties distinct in almost every aspect" (Lydon, J. Curr. Opin. Colloid Interfac. Sci. 2004, 8, 480). In particular, the isotropic to nematic transition in such phases, the consequence of stacking of dye molecules in chains, is difficult to bring into correspondence with athermal theories for rigid rods as well as modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 99 publications
2
20
0
Order By: Relevance
“…They are also evident in numerical simulations by Sidky and Whitmer [38]. Finally, NMR data and numerical simulations by Xiao et al [39] demonstrated that similar shift junctions can be observed in another LCLC Sunset Yellow; the authors concluded that the shift junctions lead to the underestimated length of the chromonic aggregates by X-ray scattering; Y-junctions were found to be of a transient nature, devolving in pairs of disconnected stacks.…”
Section: Resultsmentioning
confidence: 69%
“…They are also evident in numerical simulations by Sidky and Whitmer [38]. Finally, NMR data and numerical simulations by Xiao et al [39] demonstrated that similar shift junctions can be observed in another LCLC Sunset Yellow; the authors concluded that the shift junctions lead to the underestimated length of the chromonic aggregates by X-ray scattering; Y-junctions were found to be of a transient nature, devolving in pairs of disconnected stacks.…”
Section: Resultsmentioning
confidence: 69%
“…It is well known that organic dyes in aqueous solution tend to form stacks at high concentration, 42,57−60 and BPP has been reported to form aggregates as long as several micrometers. 42 As per our previous work on the Sunset Yellow dye, 61 we calculated the free energy to separate two BPP molecules in water using metadynamics simulations. 54 The computed binding free energy is −31.5 or −35.5 kJ/mol ( Figure S1), depending on the choice of collective variable, which is similar to the value for Sunset Yellow (−28 kJ/mol 61 ) The Journal of Physical Chemistry C Article and an experimental estimate (∼−26 kJ/mol 42 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…60 Interestingly, recent structural studies of sunset yellow support the existence of stacking features in the form of lateral shis. 64 The stacking defects illustrated in Fig. 7 are polar.…”
Section: B Viscositiesmentioning
confidence: 99%